2006
DOI: 10.1108/01437730610641331
|View full text |Cite
|
Sign up to set email alerts
|

Leadership development: does it make a difference?

Abstract: PurposeThis paper seeks to examine the impact of a leadership development programme provided for, and funded by, the NHS.Design/methodology/approachIt analyses the context, process of delivery and outcomes of the programme in the light of relevant leadership research. The programme itself is described after some consideration of the literature. Although the programme was originally commissioned by the NHS Leadership Centre for Human Resource (HR) professionals from the NHS, it is now offered to any aspiring or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 27 publications
1
47
0
2
Order By: Relevance
“…leadership development programmes (Alimo-Metcalfe & Lawler 2001, Boaden 2006, where organizational restructuring made it difficult for participants to move forward with planned leadership initiatives. During restructuring, the 'political climate' can influence leadership outcomes (Boaden 2006). This study showed that project successes strongly depended on the presence of mentoring and organizational supports.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…leadership development programmes (Alimo-Metcalfe & Lawler 2001, Boaden 2006, where organizational restructuring made it difficult for participants to move forward with planned leadership initiatives. During restructuring, the 'political climate' can influence leadership outcomes (Boaden 2006). This study showed that project successes strongly depended on the presence of mentoring and organizational supports.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Generic or universal competencies form the core of many nursing leadership development programmes (Alimo‐Metcalfe & Lawler 2001). Although there is supporting evidence for some universal competencies, such as communications and teamwork (Boaden 2006), constantly evolving healthcare demands necessitate additional leadership competencies, such as knowledge management, technology use and globalization (Huston 2008). Without a unifying theoretical framework of significance to nursing practice and research, myriad of competency combinations and delivery methods will arise – making it difficult to know what aspects of leadership development programmes are most effective for nurse leaders.…”
Section: Introductionmentioning
confidence: 99%
“…The data suggested that the majority had made a positive impact operationally. We found, like Boaden (2006) that many participants were better placed to utilise evidence effectively which is a factor not often cited in the leadership literature. Participants were evidently using their learning to take an enquiry approach in order to solve problems and address complex issues.…”
Section: Nine Projects Related To Organisational Changementioning
confidence: 51%
“…Many programmes are only evaluated through ‘happy sheets’ circulated at the end of individual sessions or modules, but in addition to being evaluated in this way ( reactions ), this programme is also evaluated through the knowledge gained by participants; the workplace behaviours they exhibit during and postprogramme; and the impact of those changes on the organization ( results ). This model has been used for the evaluation of other programmes (Boaden 2005). The source of the data used for the evaluation is shown in Table 2.…”
Section: The Training Programmementioning
confidence: 99%